Refleksi Pendekatan Hermeneutika dalam Pengembangan Pendidikan Islam - Habibi, Hasbi; Hadi, Rahmat (Asosiasi Mahasiswa Program Pascasarjana | Universitas Islam Darussalam (UID) | Islamic University of Darussalam | Ciamis | Jawa Barat, 2023)
The concept of adopting a hermeneutic approach in modern Islamic education remains an ongoing endeavor, evolving in response to intellectual contributions that shape novel theories for the advancement of Islamic education on a global scale. The objective of this literary analysis is to ascertain the pertinence of the hermeneutical approach to Islamic education. The research approach employed in this work utilizes qualitative methodology. A comprehensive analysis was conducted utilizing the content analysis method in descriptive analysis. Hermeneutics is a process of rigorous analysis aimed at interpreting text or reality in order to comprehend its significance. The optimal approach to foster progress in Islamic education is to challenge and transform outdated beliefs by cultivating a mindset focused on continuous growth. In addition, it is imperative to reform the administration of Islamic education to ensure professionalism in all departments and units of educational institutions, while also considering ideological and ethnic diversity. Nevertheless, it is imperative to cultivate a profound appreciation for the extraordinary nature and unique qualities of the Al-Qur'an, which must be consistently preserved.